Pengembangan Materi Sastra Berbasis Cerita Rakyat Asal Usul Way Linti dan Asal Usul Kuto Bumi - Ana Juwita; Edi Suyanto; Munaris Munaris (Universitas Lampung, 2018)
The purpose of this research is (1) to produce the product of literature teaching materials based on folklore Asal Usul Way Linti and Asal Usul Kuto Bumi to understand the values of character of junior high school students of class VII, (2) to describe the feasibility of literary materials based on folklore Asal Usul Way Linti and Asal Usul Kuto Bumi. This research is a development research (RD). The result of the research shows that (1) has been developed a textbook of literature folklore Asal Usul Way Linti and Asal Usul Kuto Bumi with the title of book